Fire in the streets - Magoon, Kekla (Aladdin, 2013)
In the aftermath of Dr. King's assassination in 1968, Chicago fourteen-year-old Maxie longs to join the Black Panthers, whether or not her brother Raheem, ex-boyfriend Sam, or her friends like it, and is soon caught up in the violence of anti-war and civil rights demonstrations.